(3JfhjQ GdebHGS ef JaSjQ GHf YHGSs - (3GdTjQGRj, GdajQhRBHGOj, CHh WGgQ, eLO GdOjf, eMeO Hf jYbhH Hf eMeO Hf EHQGgje (B((3, J (B817 (3g`(B)s ((3CMeO, GdeYQha HUhdGb RGOgs)
(3ChdgG (B:s
(3hUdi Gddg Ydi NjQ Ndbg CNHQfG YHO Gddg GdTYI Hf GdeCehf GdgQhj Yf eMeO Hf eQhGf Yf GdcdHj Yf CHj UGdM Yf GHf YHGS; bGd(B: (3Gddg hHgLJg hHOGAg hHQcJg hSehg Cj GQJaGYgs
(3BNQgG (B:s
(3jhShS aj UOhQ GdLf ceG jhShS ceG jhShS aj UOhQ GdfGS fRdJ gGJGf GdUhQJGf aj TCf dHjO Hf YGUe hGdTcQ hGdefI ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/147s
(3cTa GdXfhf (B1/502s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs